Does the advanced cardiovascular life support (ACLS) training course improve the outcome of resuscitation in the Emergency Department? - Wittayachamnankul, Borwon; Chenthanakij, Boriboon; Sruamsiri, Kamphee; Sairai, Phatsawan (Biomedical Sciences and Clinical Medicine, 2024)
Background The advanced cardiac life support (ACLS) provider course is designed to train medical professionals to master their skills in standard cardiopulmonary resuscitation (CPR) for use in their daily occupation, whether in or out of hospital. This course was set up in 2009 at Maharaj Nakorn Chiang Mai Hospital, Faculty of Medicine, Chiang Mai University for physicians and nurses who work in critical care units. Objective To assess the impact of ACLS provider course implementation on the survival rate of patients undergoing cardiopulmonary resuscitation in the Emergency Department, Maharaj Nakorn Chiang Mai Hospital. Method A retrospective study was carried out from January 2006 to December 2008, and January 2010 to December 2012 to compare patient survival rates before and after 2009, when ACLS provider course training was implemented. Primary endpoints included return of spontaneous circulation (ROSC), 24-hour survival and survival to discharge. Data analysis calculated survival outcome by using the Chi-square test, with p <0.05 used as a signifi cance level. Result Events of cardiac arrest in this study totaled 1,031, of which 486 occurred before the course was implemented. Fifty one percent and 48.81% of these patients had ROSC before and after implementation of the course, respectively (p =0.49), while their survival at 24 hours was 15.43% and 20.73%, respectively (p =0.029), and survival to discharge 7.41% and 8.44%, respectively (p =0.56). Conclusion The ACLS training course could improve 24-hour survival in hospital for patients who underwent CPR, but did not improve patient survival to discharge.